An Efficient Micropropagation Protocol For Mucuna Pruriens (L.) Dc. - Karim, MR; Bhadra, SK; Rahman, MM (Chittagong University Journal of Biological Sciences, 2024)
An efficient protocol was developed for rapid micropropagation of Mucuna pruriens (L.) DC., an important medicinal plant species of Bangladesh. For the purpose, leaf segments, nodal segments and shoot apices of in vitro grown seedlings and cotyledon segments of immature seeds of field grown plants were cultured on agar solidified MS medium supplemented with different combinations of PGRs (Plant Growth Regulators). Only leaf and cotyledon segments produced light green to green friable/ compact callus in some of the media combinations. Combination and concentration of PGRs played important role in induction of such tissue. The induced tissues failed to differentiate on further culture in a wider spectrum of PGR supplemented media. On the other hand nodal segments and shoot apices produced multiple shoot buds when grown on a wide range of PGRs (BAP, NAA, IAA, Kn) supplemented media. Maximum number of multiple shoot buds were produced in medium containing 1.5 mg/l BAP + 1.0 mg/l IAA. The elongated shoot buds on further culture in rooting media produced strong and stout root systems. Half strength MS media fortified with either 1.0 mg/l IAA or 2.0 mg/l IAA was most effective for induction and proliferation of roots. These complete plantlets were successfully acclimatized and established in outside pots through a successive phase of acclimatization. The Chittagong Univ. J. B. Sci.,Vol. 7(1 &2):79-89, 2012.